A comparison between the pathophysiology of multiple sclerosis and normal pressure hydrocephalus: is pulse wave encephalopathy a component of MS?. Issue 1 (December 2016) - Bateman, Grant; Lechner-Scott, Jeannette; Lea, Rodney
Abstract Background It has been suggested there is a chronic neurodegenerative disorder, underlying the pathophysiology of multiple sclerosis (MS), which is distinct from the more obvious immune-mediated attack on the white matter. Limited data exists indicating there is an alteration in pulse wave propagation within the craniospinal cavity in MS, similar to the findings in normal pressure hydrocephalus (NPH). It is hypothesized MS may harbor pulse wave encephalopathy. The purpose of this study is to compare blood flow and pulse wave measurements in MS patients with a cohort of NPH patients and control subjects, to test this hypothesis. Methods Twenty patients with MS underwent magnetic resonance (MR) flow quantification techniques. Mean blood flow and stroke volume were measured in the arterial inflow and venous out flow from the sagittal (SSS) and straight sinus (ST). The arteriovenous delay (AVD) was defined. The results were compared with both age-matched controls and NPH patients. Results In MS there was a 35 % reduction in arteriovenous delay and a 5 % reduction in the percentage of the arterial inflow returning via the sagittal sinus compared to age matched controls. There was an alteration in pulse wave propagation, with a 26 % increase in arterial stroke volume but 30 % reduction in SSS and ST stroke volume. The AVD and blood flow changes were in the same direction to those of NPH patients. Conclusions There are blood flow and pulsation propagation changes in MS patients which are similar to those of NPH patients. The findings would be consistent with an underlying pulse wave encephalopathy component in MS.